2020
DOI: 10.1097/md.0000000000020851
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous subepithelial hemorrhage of renal pelvis and ureter (Antopol-Goldman lesion) in hemophilia A patient with inhibitor

Abstract: Introduction: The Antopol-Goldman lesion (AGL), which expresses subepithelial hemorrhage in the renal pelvis, was first defined by Antopol and Goldman in 1948. The objective of this study is to report the first case of AGL in patients with congenital hemophilia and review the relevant literature. Patient concerns: A 32-year-old male patient diagnosed with congenital hemophilia A (FVIII = %4) with high responding inhibitors (7.4 BU) was admitted to our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…Similarly, adjustment for differences in the assessment periods of the two studies could not be included in the analysis, as these data were not available for PROTECT VIII. Furthermore, detailed clinical data for the patients in these studies are limited, and information on, for example, spontaneous bleeds such as the recently reported case of a spontaneous subepithelial haemorrhage (Antopol-Goldman lesion) in the renal pelvis and ureter of a patient with haemophilia A and inhibitors [ 25 ]. The absence of a placebo group in these clinical studies means that there can be no adjustment for residual confounding; other confounding factors not reported in the trials may also have an influence on the results reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, adjustment for differences in the assessment periods of the two studies could not be included in the analysis, as these data were not available for PROTECT VIII. Furthermore, detailed clinical data for the patients in these studies are limited, and information on, for example, spontaneous bleeds such as the recently reported case of a spontaneous subepithelial haemorrhage (Antopol-Goldman lesion) in the renal pelvis and ureter of a patient with haemophilia A and inhibitors [ 25 ]. The absence of a placebo group in these clinical studies means that there can be no adjustment for residual confounding; other confounding factors not reported in the trials may also have an influence on the results reported here.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inhibitors observed in around one-third of patients with congenital hemophilia A have different kinetic features compared to anti-FVIII antibodies found in acquired hemophilia A. However, in both cases, the interference of these antibodies with FVIII replacement therapy leads to the need of bypassing agents [19]. Indeed, in the case of inherited bleeding disorders such as hemophilia A and B and VWD, when plasma levels of FVIII are markedly reduced, joint bleeding is a typical presentation [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…UTUCs are another kind of common renal pelvis malignant tumor. Patients with UTUCs typically have a history of hematuria[ 11 ]. In contrast, symptoms of renal pelvis SFTs are mostly due to pressure effect of the lesion, and these patients rarely develop urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%